2001
DOI: 10.1002/1096-9896(2000)9999:9999<::aid-path745>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Differences in genetic alterations between primary lobular and ductal breast cancers detected by comparative genomic hybridization

Abstract: Infiltrating ductal (DC) and lobular carcinoma (LC) of the breast represent the most frequently observed varieties of invasive breast cancer, characterized by differences in their histological and clinical properties. Although comparative genomic hybridization (CGH) of invasive breast carcinomas has revealed a complex and consistent pattern of DNA copy number changes, the data with regard to type specific aberrations are limited. A comprehensive study was therefore performed on 19 LCs and 29 DCs to ascertain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 29 publications
7
43
0
2
Order By: Relevance
“…The higher rate of 8p deletions in NST as compared to lobular cancer is not surprising as most genomic alterations are more frequent in NST than in lobular carcinomas such as amplifications of HER2, 41,49 MYC, 41 MDM1, 41 and AIB1, 50 or overexpression of p53. 51 A higher rate of 8p deletions in NST than in lobular carcinomas has earlier been suggested by data from Guenther et al 52 finding loss of 8p in 28% of NST but only in 5% of lobular carcinomas (p D 0.05) and by Thor et al 53 reporting 8p in 33% of NST but only in 13% of lobular carcinomas (p D 0.12). Given the general link of 8p deletions with unfavorable disease outcome, the high rate of 8p deletions in papillary cancer and cancers with medullary features was unexpected.…”
Section: Discussionmentioning
confidence: 88%
“…The higher rate of 8p deletions in NST as compared to lobular cancer is not surprising as most genomic alterations are more frequent in NST than in lobular carcinomas such as amplifications of HER2, 41,49 MYC, 41 MDM1, 41 and AIB1, 50 or overexpression of p53. 51 A higher rate of 8p deletions in NST than in lobular carcinomas has earlier been suggested by data from Guenther et al 52 finding loss of 8p in 28% of NST but only in 5% of lobular carcinomas (p D 0.05) and by Thor et al 53 reporting 8p in 33% of NST but only in 13% of lobular carcinomas (p D 0.12). Given the general link of 8p deletions with unfavorable disease outcome, the high rate of 8p deletions in papillary cancer and cancers with medullary features was unexpected.…”
Section: Discussionmentioning
confidence: 88%
“…In a recent study, we have proposed the existence of a family of low grade breast carcinoma, suggesting a developmental pathway from normal to precursor to breast carcinoma [3]. We and others [4][5][6][7] have confirmed a high association between LCIS and the development of ILC. Therefore, its detection and treatment substantially improves survival [1].…”
Section: Introductionmentioning
confidence: 73%
“…16q loss is seen with a similar high frequency in LCIS, ILC, tubular cancer, and in low and intermediate DCIS, whereas high grade invasive or in situ ductal carcinomas shows 16q loss much less frequently [4,5,9]. The loss of 16q regions is believed to be an early genetic event in the development of invasive breast cancer from in situ lesions [6].…”
Section: Introductionmentioning
confidence: 98%
“…Our results suggest that HER2/neu gene amplification is of minor importance in the development or progression of invasive lobular carcinoma regardless of grade, in contrast with invasive ductal carcinomas. Molecular characterization of invasive lobular carcinomas has shown that they have a higher incidence of loss of chromosome 17q than ductal carcinomas (P ¼ 0.3) and that ductal tumors have a higher incidence of 17q22-24 amplification than their lobular counterparts, 54 factors that may influence HER2/neu gene copy number and hence protein expression. A cDNA microarray study similarly showed that only two of 17 lobular carcinomas arrayed displayed HER2/neu gene overexpression.…”
Section: Discussionmentioning
confidence: 99%